Broadening visions of BPR : the imperative of strategic integration - Peppard, Joe (Cranfield University, 1995)
This paper calls for BPR to adopt a more strategic context suggesting that such a strategic perspective must be adopted if progress is to be made. In order to frame this position, the paper first takes the reader on an excursion through the BPR literature beginning by briefly examining how BPR has developed over the last five years and focusing on some of the central debates. Second, it suggests that BPR is broadening in perspective and examines developments which are contributing to a new conceptualisation. Finally, the paper points to the need for greater strategic integration, a call which is being highlighted by organisations’ experiences with BPR. However, in order to achieve this the paper proposes the need to articulate a process theory of the firm.
Keywords: Business process re-engineering